(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The idea of progress in entrepreneurship involves providing individuals with the data and information needed to create a large company and refining his entrepreneurship skills. Today, entrepreneurship development programs are an important means of industrialization and are treated as a response to India’s unemployment problem. In this paper, efforts have been made to consider the process of developing entrepreneurship (ED) in India and the work of business development programs in the country’s financial development. The information used for the final purpose of this study is basically from an ancillary source.